Our iceberg is melting : changing and succeeding under any conditions - Kotter, John P., 1947- (St. Martin's Press, 2006)
In this business management fable, one penguin notices something problem that could become a big problem for the whole colony, but the other penguins don't want to listen, so he must convince and enlist the help of others to get something done.